Long-term outcomes and determinants of restenosis after renal artery angioplasty in hypertensive patients with renovascular disease. (25th November 2020) - Roslawiecka, A; Kablak-Ziembicka, A; Badacz, R; Pieniazek, P; Rzeznik, D; Trystula, M; Przewlocki, T
Abstract: Introduction: Restenosis (RS) following percutaneous angioplasty (PTA) of renal artery stenosis (RAS) might have an unfavorable impact on renal function and blood pressure (BP) outcomes. Aim: To evaluate prevalence and predictors of RS in patients treated with PTA for RAS, and relationship between BP and renal function (RF) changes with RS. Material and methods: We analyzed freedom from RS in 210 patients (64.6±12.8; range:20–85y.o.), who underwent 248 successful stent-assisted PTAs in RAS. The change in levels of serum creatinine (SCC), eGFR, systolic/diastolic BPs (SBP/DBP) were analyzed prior to PTA, at 6-, 12-months and final follow-up visits, and whenever RS was diagnosed. Results: RS was identified in 30 (14.3%) patients and 36 (14.5%) lesions. The Kaplan-Meier RS-free survival curves in fibromuscular dysplasia, atherosclerosis and vasculitis were: 100% and 100%; 95.6 and 83.9%, while 71.4 and 39.7% at 1 and 7-years, respectively. Patients with RS, as compared to RS-free patients, presented with lesser response in changes of: SBP (1.4±17.6 vs −15.8±25.8mmHg; p=0.01), DBP (2.64±10.1 vs. −6.5±14.1mmHg; p=0.002), SCC (22.4±55.2 vs −3.6±43.9μmol/L; p=0.002) and eGFR (−1.85±18 vs. −5.34±19.5mmHg; p=0.045). In multivariate Cox regression analysis, independent predictors of RS occurred: lack of BP decrease (HR: 4.19, 95% CI: 1.67–10.3; p=0.002), lack of eGFR increase of less than ≤0.17 ml/min/1.73m 2 (HR: 2.93, 95% CI: 1.08–7.91; p=0.033), stent diameter ≤5mm (HR: 2.76, 95% CI: 1.09–6.97; p=0.031) and vasculitis (HR: 5.61, 95% CI: 1.83–17.2; p=0.003). RS was treated in 24 patients with RS recurrence in 20%. Conclusions: RS rate differs depending on RAS etiology. Lack of SBP/DBP and eGFR improvement, vasculitis, and stent diameter are associated with RS risk. Repeated PTA is effective, but recurrent RS occurs in 20% of cases. Funding Acknowledgement: Type of funding source: None